Tectonics Modulated Long‐Term Weathering Inputs From the East Asian Continent and Tropical Island Arc to the South China Sea Since the Late Oligocene - Mengjun Li; Christophe Colin; Shiming Wan; Zhaojie Yu; Zhimin Jian; Zehua Song; Arnaud Dapoigny; Hualong Jin; Jin Zhang; Debo Zhao; Anchun Li (Geophysical Research Letters)
Abstract The chemical weathering of Earth's silicate rocks regulates the global climate. However, the exact role of continental weathering with orogenic building and island arc weathering with arc‐continent collisions remains unclear. Here, we established a seawater neodymium isotopic composition (εNd) record for the northern South China Sea (SCS) since 28 Ma, retrieving from planktonic foraminifera at International Ocean Discovery Program Site U1501. The progressively restricted SCS connection from the Pacific Ocean and intensified weathering inputs from the East Asian Continent correspond to an unradiogenic trend of εNd records between 17 and 9 Ma. The radiogenic trend of εNd records since 9 Ma could be induced by enhanced tropical island arc weathering inputs in the context of the Luzon Arc‐Eurasian Continent collision, which resulted in significant atmospheric CO2 consumption. This study highlights that enhanced weathering of tropical island arc potentially significantly contributed to global cooling since the late Miocene.